PENGARUH STATUS SOSIAL EKONOMI TERHADAP PRESTASI MAHASISWA PERGURUAN TINGGI SWASTA - Muliyadi Jaya; Pamungkur Pamungkur (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2016)
The achievement of university students is influenced by their socio-economic status as a result of the interactions between their socio-economic positions, work experiences, and families which react relatively on each other in relation to their incomes, occupations, and academic degrees. This study was conducted to investigate socio-economic status as the factor that influences the academic achievement of private university students. Furthermore, this socio-economic status factor divides parenting in relationship with children development into two distinct ways. A family that has low rate of income theoretically will be inclined to raise a child in lack of capability to afford excellence academic accomplishments. Accordingly, the objective set for this study was to find out the influence of socio-economic status on the academic achievement of private university students in Palangka Raya. Therefore, this study applied multivariate analysis to verify the influence of the socio-economic status of family on children’s academic accomplishments. This study also investigated the impact of age, gender, marriage status, income, region, education, and socio-economic status of the parents based on cross-section data collected in 2012 and 2015. Meanwhile, the result of this study was obtained from random sampling collected from three different private universities in Palangka Raya using questionnaire. Thus, the result attained from this study was that a stable socio-economic status has a meaningful influence on academic achievement of the students at private universities in Palangka Raya. In addition, a higher socio-economic status brings out some advantages to the students of private universities in Palangka Raya.